Regionally Distinct Astrocytes Display Unique Transcription Factor Profiles in the Adult Brain - Lozzi, Brittney; Huang, Teng-Wei; Sardar, Debosmita; Huang, Anna Yu-Szu; Deneen, Benjamin (Frontiers in Neuroscience, 2020)
Astrocytes are the most abundant type of glial cell in the central nervous system and perform a myriad of vital functions, however the nature of their diversity remains a longstanding question in neuroscience. Using transcription factor motif discovery analysis on region-specific gene signatures from astrocytes we uncovered universal and region-specific transcription factor expression profiles. This analysis revealed that motifs for Nuclear Factor-I (NFI) are present in genes enriched in astrocytes from all regions, with NFIB and NFIX exhibiting pan-astrocyte expression in the olfactory bulb, hippocampus, cortex, and brainstem. Further analysis into region-specific motif patterns, identified Nkx3-1, Smad4, Pgr, and Nkx6-1 as prospective region-specific transcription factors. Validation studies revealed that Nkx6-1 is exclusively expressed in astrocytes in the brainstem and associates with the promoters of several brainstem specific target genes. These studies illustrate the presence of several transcriptional layers in astrocytes across diverse brain regions and provide a new entry point for examining how astrocyte diversity is specified and maintained.